Enhancement of Atorvastatin Tablet Dissolution Using Acid Medium - j.Hasson, Kahtan (Iraqi Journal of Pharmaceutical Sciences, 2017)
In this study some generic commercial products of Atorvastatin tablets were evaluated by dissolution test in acid medium by comparing with that of parent drug Lipitor of Pfizer Company. Some of solubilizing agents were studied in formulation of Atorvastatin tablet including; surface active agent and PEG 6000 .The most effective factor was the use of PEG6000 in formulation of Atorvastatin tablet which improved the dissolution and the results of dissolution profile of formulated tablet in this work was bioequivalent to that of Lipitor .The quantitative analysis of this work was performed by using reversed phase liquid chromatography and a proper mixture of mobile phase which give a retention time for Atorvastatin about 6 minutes .